2015
DOI: 10.1097/mbc.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Association of selenoprotein S gene polymorphism with ischemic stroke in a Chinese case–control study

Abstract: Previous studies showed that selenoprotein S (SELS) was associated with a range of inflammatory markers, and its gene expression was influenced by a polymorphism in the promoter region. The genetic basis of the ischemic stroke has now been largely determined, so the aim of the study was to examine the role of SELS genetic variants in the ischemic stroke risk in a Chinese population. We conducted a case-control study with 239 ischemic stroke patients and 240 controls. Two single-nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…There is an increasing number of studies showing the role of selenoprotein gene variants in CVD. The SELENOS SNPs in the promoter region were linked to the development of diabetes [ 24 ], ischemic stroke [ 21 , 22 ], coronary heart disease [ 22 , 23 ], as well as carotid and coronary atherosclerosis [ 23 ]. The SEPP1 rs3877899 and rs7579 SNPs have been associated with metabolic phenotypes related to diabetes [ 28 ], while different GPX4 variants were linked with the concentration of inflammatory biomarkers [ 27 ], glutathione peroxidase activity [ 45 ], lipid metabolism [ 46 ], as well as obesity [ 45 ], cerebral stroke [ 25 ], and endothelial dysfunction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing number of studies showing the role of selenoprotein gene variants in CVD. The SELENOS SNPs in the promoter region were linked to the development of diabetes [ 24 ], ischemic stroke [ 21 , 22 ], coronary heart disease [ 22 , 23 ], as well as carotid and coronary atherosclerosis [ 23 ]. The SEPP1 rs3877899 and rs7579 SNPs have been associated with metabolic phenotypes related to diabetes [ 28 ], while different GPX4 variants were linked with the concentration of inflammatory biomarkers [ 27 ], glutathione peroxidase activity [ 45 ], lipid metabolism [ 46 ], as well as obesity [ 45 ], cerebral stroke [ 25 ], and endothelial dysfunction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, interactions with the manganese superoxide dismutase gene ( SOD2 ) variants are observed the most frequently [ 18 20 ]. There is also growing evidence on the role of polymorphisms in selenoprotein genes in CVDs [ 21 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…106,107 A substitution C > T occurs in the promoter region of the SELENOS gene (rs34713741) that has been associated with an increased risk of rectal, 102 colorectal, and gastric cancer 108 as well as ischemic stroke. 109 Another relevant polymorphism is the rs28665122, located in the promoter region of the SELENOS gene, also known as -105G/A. This SNP has been correlated with plasma IL-1, IL-6, and TNF-α levels 106 , an increased susceptibility to Hashimoto´s Thyroiditis 110 , preeclampsia in Norwegian women 107 and an increased risk of gastric cancer.…”
Section: Evidence Of the Functional Consequences Of Some Single Nucleotide Polymorphisms In Selenoproteinsmentioning
confidence: 99%
“…However, they found that the risk ratio of the development of CVD in females carrying SELENOS SNP rs8025174 was 2.95; the risk ratio of the development of ischemic stroke in the population carrying SNP rs7178239 was 1.75, and the risk ratio in females reached 3.35. Li et al [ 73 ] used the Chinese population as subjects to perform a case-controlled study (ischemic stroke group n = 239; non-ischemic stroke control group n = 240) and showed that SELENOS SNP rs4965814 could increase the risk of ischemic stroke by 1.54-fold; this risk ratio in females reached 2.43. These results were similar to those of Silander et al [ 74 ].…”
Section: Selenos and Macrovascular Diseasesmentioning
confidence: 99%